Novel Mouse Tauopathy Model for Repetitive Mild Traumatic Brain Injury: Evaluation of Long-Term Effects on Cognition and Biomarker Levels After Therapeutic Inhibition of Tau Phosphorylation - Rubenstein, Richard; Sharma, Deep R.; Chang, Binggong; Oumata, Nassima; Cam, Morgane; Vaucelle, Lise; Lindberg, Mattias F.; Chiu, Allen; Wisniewski, Thomas; Wang, Kevin K. W.; Meijer, Laurent (Frontiers in Neurology, 2019)
Traumatic brain injury (TBI) is a risk factor for a group of neurodegenerative diseases termed tauopathies, which includes Alzheimer’s disease and chronic traumatic encephalopathy (CTE). Although TBI is stratified by impact severity as either mild (m), moderate or severe, mTBI is the most common and the most difficult to diagnose. Tauopathies are pathologically related by the accumulation of hyperphosphorylated tau (P-tau) and increased total tau (T-tau). Here we describe: (i) a novel human tau-expressing transgenic mouse model, TghTau/PS1, to study repetitive mild closed head injury (rmCHI), (ii) quantitative comparison of T-tau and P-tau from brain and plasma in TghTau/PS1 mice over a 12 month period following rmCHI (and sham), (iii) the usefulness of P-tau as an early- and late-stage blood-based biochemical biomarker for rmCHI, (iii) the influence of kinase-targeted therapeutic intervention on rmCHI-associated cognitive deficits using a combination of lithium chloride (LiCl) and R-roscovitine (ros), and (iv) correlation of behavioral and cognitive changes with concentrations of the brain and blood-based T-tau and P-tau. Compared to sham-treated mice, behavior changes and cognitive deficits of rmCHI-treated TghTau/PS1 mice correlated with increases in both cortex and plasma T-tau and P-tau levels over 12 months. In addition, T-tau, but more predominantly P-tau, levels were significantly reduced in the cortex and plasma by LiCl + ros approaching the biomarker levels in sham and drug-treated sham mice (the drugs had only modest effects on the T-tau and P-tau levels in sham mice) throughout the 12 month study period. Furthermore, although we also observed a reversal of the abnormal behavior and cognitive deficits in the drug-treated rmCHI mice (compared to the untreated rmCHI mice) throughout the time course, these drug-treated effects were most pronounced up until 10 and 12 months where the abnormal behavior and cognition deficits began to gradually increase. These studies describe: (a) a translational relevant animal model for TBI-linked tauopathies, and (b) utilization of T-tau and P-tau as rmCHI biomarkers in plasma to monitor novel therapeutic strategies and treatment regimens for these neurodegenerative diseases.